A LITERATURE REVIEW IN TRIAGE DECISION MAKING: SUPPORTING NOVICE NURSES IN DEVELOPING THEIR EXPERTISE - Kurnia Putri Yuliandari (Belitung Nursing Journal, 2019)
Emergency nurses often find themselves doing triage under time pressure and with only limited information, while the accuracy and rapidity of triage assessment may well determine a patient’s safety. A question may emerge as to whether novice nurses, who may have lack of experience and knowledge, could deal with such a demanding practice. Equipping novice nurses with important aspects in triage decision-making processes is pivotal. The aim of this literature review is to identify potential elements that could be utilised as supports for novice nurses in developing their expertise of making decision in triage. This study employed CINAHL, ScienceDirect, and PsycINFO to find relevant articles, using search terms “triage”, “decision-making”, “clinical decision-making”, combined with “expert”, and “novice”. The publication dates of those articles ranged from 1990 to 2015. 1487 articles was found and sorted based on inclusion and exclusion criteria, resulting in seventeen articles that had been used in this study. Literature review suggests four important elements for developing novices’ expertise in triage decision making: understanding the difference of novices’ and experts’ performance, critical analysis on theoretical approaches of clinical decision-making processes, defining factors that may influence nurses’ triage decision making, understanding errors that might be made by novices, and using appropriate learning strategies.